Effects of fermented chicken manure products on the N mineralization rate of the soil using the incubation method - Tóth, Florence Alexandra; Tamás, János; Nagy, Péter Tamás (Acta Agraria Debreceniensis, 2022)
In our study, the effect of fermented and specially added poultry manure products (superabsorbent polymer (SAP), bentonite and Aegis as a mycorrhizal inoculum) were investigated in a short soil incubation experiment – at 60% water capacity level - on sandy soil. Soil samples were collected from two layers of the incubation pots after the second and fourth week to check the status of the tested products and the processes in the soil. The pH and the electric conductivity (EC) of the samples were measured using an electrochemical method, while the ammonium and nitrate content of the samples was determined with a photometric method. Soil pH and EC values slightly were decreased during the experiment. Our results pointed out that the increasing dose of SAP caused lower soil pH. The nitrate content of the soil did not change significantly during the experiment. It was found that the increasing SAP content in the products, due to its cross-linked structural property, protected the nitrate ions from leaching. Our results suggest that applied SAP does not bind the nutrient ions so tightly in its structure that it competes with the plant for uptake.